TOURISM IN NAGALAND – A BRIEF STUDY - Dr. Sanjay Kumar Chhabra (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2022)
With the opening of the state to the international tourist by relaxation of Restricted Area Permit (RAP), a good number of foreign tourists, as well as domestic tourists visit Nagaland every year. By whatever name people have called this realm, hidden among the mountains of India’s northeast, Nagaland has always evoked a sense of mysticism and awe, intensified by the remoteness of its geographical location. Spirits that roam the jungles & villages, the fertility of mother earth, social bonding among communities, rejuvenation etc are the main elements that form the souls of the Naga people. Although by virtue of her natural beauty, the whole of Nagaland is a tourist hotspot, yet certain exceptionally charming places have been identified and developed by the Government to promote tourism in Nagaland e.g. wild life sanctuaries and national parks, namely, Intanki and Puliebadze in Kohima District, Fakim in Tuensang and Rangapahar in Dimapur.